Artificial Intelligence and Education: Examining Ethical Awareness and Social Responsibility in Classroom Applications - Agustini; Danellie C. Llamas (Educational Dynamics: International Journal of Education and Social Sciences, 2024)
Artificial Intelligence (AI) has increasingly become an integral component of modern education, offering significant opportunities to improve accessibility, efficiency, and personalized learning. This study explores students’ perceptions of AI in educational contexts, focusing not only on its practical benefits but also on ethical concerns, particularly regarding data privacy and social responsibility. Adopting a mixed-method design, the research collected data through surveys and classroom observations. The survey responses were analyzed using descriptive statistics to identify trends in perceptions, while observation notes were thematically coded to capture students’ real interactions with AI applications. The findings reveal that students generally exhibit a positive attitude toward AI, recognizing its potential to enhance learning experiences by making education more accessible and efficient. However, the study also highlights that concerns over data privacy and the potential misuse of information remain central issues. Moreover, a notable gap exists between students’ appreciation of the practical benefits of AI and their awareness of ethical dimensions such as algorithmic bias and digital responsibility. This imbalance suggests that while students are ready to embrace AI as a tool, they may not yet be adequately prepared to address the broader ethical implications of its use. The discussion situates these findings within the framework of digital ethics, emphasizing the need for education systems to integrate ethical literacy alongside technological skills. By doing so, schools and universities can ensure that students are both technologically competent and socially responsible. The study concludes that although AI is welcomed in educational settings, greater emphasis on digital ethics education is essential to maximize its benefits and minimize potential risks. This research provides a basis for future studies on policy development and ethical practices for AI in the classroom.